The Effect of Students\'Role on Parents\' Performance on Waste Disposal in Maragheh - Fatemeh Estebsari; Mohammad Hossein Taghdisi; Zahra Rahimikhalifeh kandi; Agha Fatemeh Hosseini (Mashhad University of Medical Sciences, 2017)
Background and objective: Nowadays, recycling has attracted interest as an effective method in waste management. Teaching recycling to students is of great importance due to the important role this group plays in the participation of parents. This research dealt the effects of recycling educator students on operation of parents in the separation of waste. Methods: In this quasi-experimental study, a school as the experimental group and a school as the controls group were randomly selected. The parents of students selected, 100 Person (50 in the experimental group and 50 than the control group) participated in the study. After the needs assessment by researcher, a questionnaire was developed that included question on demographic, awareness, attitude, performance, and participation of the parents. One session of discussion with these parents was held to attract their cooperation with the students and also Educational program for students in the field of waste separation was performed. Then The effect of education on parents, one month and three months after intervention in both groups were assessed by questionnaire and data analyzed in spss16 with using descriptive and analytical statistics. Results: The results showed that, after the educational intervention, Separation of recyclable waste from non-recyclable, with 58%, was the highest scores. Also, after the intervention in the experimental group mean on awareness, attitude, performance, and participation of the parent’s changes were significant (P< 0.001).        Conclusion: Findings of this research showed the positive effects of the students on their parents’ participation in recycling at source. Paper Type: Research Article.